Policy Implementation Of Stunting Prevention In Kupang Tengah District, Kupang Regency - KONAY, Djeni Ruliarita; PANDIE, David B.W.; DJANI, William (Journal of Tourism Economics and Policy, 2023)
Kupang Regency is still one of the 3 regencies in the Province of NTT with a stunting rate of 24.14 percent or 7,207 children experiencing stunting based on data for the February 2022 weighing month and one of the locations for stunting 'pockets' in Kupang Regency so that the target for reducing the prevalence of stunting in Kupang Regency In 2022 the required 16.19 percent has not been fulfilled. Therefore, this study aims to analyze the implementation of stunting prevention policies in Kupang Tengah District, Kupang Regency. This research is a qualitative descriptive study using primary and secondary data sources collected through qualitative observation, qualitative interviews, qualitative documents and qualitative audio and visual materials. then the data that has been collected is analyzed using the data analysis steps proposed by Creswell (2016: 264-268). The results of the study show that (1) the level of technical difficulty is that there is still sectoral ego and coordination that is not going well, the behavior of the target group has not complied with the policy and the proportion of the target group is relatively small to the total population. (2) The contents of the policy are clear but the implementation is bad (bad execution) and the allocation of resources is minimal. (3) environmental variables from the implementation of policies that are constrained by social, economic and technological conditions but have the support of higher officials but are not supported at the lowest level of policy.